2018
DOI: 10.3390/ijms19102971
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Coronary Artery Ectasia Compared to Atherosclerosis

Abstract: We have read with great enthusiasm the article recently published by Boles et al. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The amount of visceral fat in patients with abdominal obesity is significantly elevated, which significantly increases insulin resistance and the levels of chronic inflammatory factors, thereby causing increased morbidity of vascular diseases. 17 In the present study, there was a more substantial increase in WHR than in BMI in the T2DM þ LEAD group, demonstrating that abdominal obesity, represented by WHR, plays a greater role in DM-associated LEAD. Furthermore, SMI was closely correlated with LEAD.…”
Section: Discussionsupporting
confidence: 51%
“…The amount of visceral fat in patients with abdominal obesity is significantly elevated, which significantly increases insulin resistance and the levels of chronic inflammatory factors, thereby causing increased morbidity of vascular diseases. 17 In the present study, there was a more substantial increase in WHR than in BMI in the T2DM þ LEAD group, demonstrating that abdominal obesity, represented by WHR, plays a greater role in DM-associated LEAD. Furthermore, SMI was closely correlated with LEAD.…”
Section: Discussionsupporting
confidence: 51%
“…As was explained previously, the inflammatory process in CAE is beyond a localised atherosclerotic process. Additionally, high serum levels of several inflammatory biomarkers -including interferon-gamma, tumour necrosis factor-α, IL-1β, IL-6, and IL-8 -in CAE compared with those in CAD may be another reason for these different results 22. There might be some other probable hypothetical mechanisms for our findings.…”
mentioning
confidence: 73%
“…Thus, isolated CAE should be investigated independently of CAD to obtain further information about its underlying mechanism. 20,22 Liver transaminases, including AST and ALT, are widely used and routinely measured markers in a clinical setting. Previous studies have suggested that increased serum levels of ALT and AST are independently associated with atherosclerosis and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the enlargement of the carotid artery can be viewed as an indicator of unbalanced carotid arterial tensile stress of the ventricular-arterial system. This may be caused by synergistic aging, a chronic hemodynamic load, and proteolytic/elastolytic activity from an up-regulated pro-inflammatory status, all of which are also potential markers of heightened cardiovascular risk [39][40][41] as part of "dilating arterial disease" syndrome [42,43].…”
Section: Discussionmentioning
confidence: 99%